2022
DOI: 10.1021/acs.chemrev.1c00990
|View full text |Cite
|
Sign up to set email alerts
|

Surface Functionalization and Texturing of Optical Metasurfaces for Sensing Applications

Abstract: Optical metasurfaces are planar metamaterials that can mediate highly precise light−matter interactions. Because of their unique optical properties, both plasmonic and dielectric metasurfaces have found common use in sensing applications, enabling label-free, nondestructive, and miniaturized sensors with ultralow limits of detection. However, because bare metasurfaces inherently lack target specificity, their applications have driven the development of surface modification techniques that provide selectivity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 211 publications
0
37
0
Order By: Relevance
“…Surface modification is a widely used strategy to endow substrates with responsiveness and/or functionalities, which can be achieved via both chemical and physical approaches. Covalent functionalization commonly involves thiol chemistry (Au-SH), click chemistry (alkyne coating followed by azide–alkyne reaction), polymer brushes (initiator immobilization followed by polymerization of monomers), anchor molecules (silane, catechol, phosphate) followed by a polymer graft, 1-ethyl-3-(3-(dimethylamino)­propyl)­carbodiimide/ N -hydroxysuccinimide (EDC/NHS) linker, and so on. , Physical approaches, from the perspective of surface morphology, usually include roughening (plasma etching and mechanical roughening) and patterning (lithography, direct-writing, 3D patterning), which would not be discussed in details in this review . The following subsections would emphasize the approaches toward surface functionalization based on noncovalent molecular interactions, among which layer-by-layer assembly is first elucidated from the aspects of sensing, drug delivery, functional coatings, fuel cells, catalysis, packaging, water treatment, and so on.…”
Section: Building Functional Soft Materials Via Tunable Noncovalent I...mentioning
confidence: 99%
“…Surface modification is a widely used strategy to endow substrates with responsiveness and/or functionalities, which can be achieved via both chemical and physical approaches. Covalent functionalization commonly involves thiol chemistry (Au-SH), click chemistry (alkyne coating followed by azide–alkyne reaction), polymer brushes (initiator immobilization followed by polymerization of monomers), anchor molecules (silane, catechol, phosphate) followed by a polymer graft, 1-ethyl-3-(3-(dimethylamino)­propyl)­carbodiimide/ N -hydroxysuccinimide (EDC/NHS) linker, and so on. , Physical approaches, from the perspective of surface morphology, usually include roughening (plasma etching and mechanical roughening) and patterning (lithography, direct-writing, 3D patterning), which would not be discussed in details in this review . The following subsections would emphasize the approaches toward surface functionalization based on noncovalent molecular interactions, among which layer-by-layer assembly is first elucidated from the aspects of sensing, drug delivery, functional coatings, fuel cells, catalysis, packaging, water treatment, and so on.…”
Section: Building Functional Soft Materials Via Tunable Noncovalent I...mentioning
confidence: 99%
“…Metasurfaces alter the optical characteristics of a light beam, such as phase, intensity, polarization, and shape, exhibiting unprecedented electromagnetic domain properties. All-dielectric metasurface-based optical devices have been used as highly sensitive optical platforms for the reliable and rapid detection of biomolecules. They exploited the resonant wavelength shift of these devices, which were kept in close contact with a biomolecule, for their strong light-matter interaction at subwavelength scales. , In conformance with a lab-on-a-chip and micro total analysis system, , metasurface-integrated optofluidic devices help develop a miniaturized biosensing system featuring an expedited real-time chemical analysis . Recently reported metasurface-based biosensing approaches leveraged the hyperspectral multipixel imaging of the spectral resonance shift in the meta-atoms of an all-dielectric device with a high-Q-factor resonator and the analysis of the captured images using complex computation techniques; , this has initiated the development of compact spectrometer-free biosensors.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, several interesting reviews on MSs can be found which are highly recommended to readers. For instance, in [ 51 ], the most recent developments in material-specific surface functionalization and texturing are discussed as they are applied to sample optical MSs. Detailed instructions for the widespread implementation of this approach are also provided, along with an understanding of the underlying chemistry that powers functionalization and texturing operations.…”
Section: Introductionmentioning
confidence: 99%